2006
DOI: 10.1038/emm.2006.56
|View full text |Cite
|
Sign up to set email alerts
|

Increase of NKG2D ligands and sensitivity to NK cell-mediated cytotoxicity of tumor cells by heat shock and ionizing radiation

Abstract: In this study, we have investigated if current cancer therapeutic modalities including hyperthermia and ionizing radiation can increase the expression of NKG2D ligands in human cancer cell lines. The expressions of NKG2D ligands were induced by both heat shock and ionizing radiation in various cell lines including KM12, NCI-H23, HeLa and A375 cells with peaks at 2 h and 9 h after treatment, respectively, although inducibility of each NKG2D ligand was various depending on cell lines. During the induction of NKG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
104
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(110 citation statements)
references
References 48 publications
(46 reference statements)
1
104
1
1
Order By: Relevance
“…Given this observation, it seems likely that the efficacy of these mAb when delivered in combination with radiotherapy is through blockade of PD-1/PD-L1 signaling and not mediated through the PD-L1/CD80 or PD-1/PD-L2 axes although further experiments are needed to confirm this. In addition to generating adaptive immunity, radiotherapy has been shown to enhance recognition and antitumor activity of NK cells through increased tumor cell expression of NKG2D (29). Our data reveal that the depletion of NK cells reduced local tumor control at early time points (up to 11 days after completion of radiotherapy) but did not affect overall survival.…”
Section: Discussionmentioning
confidence: 48%
“…Given this observation, it seems likely that the efficacy of these mAb when delivered in combination with radiotherapy is through blockade of PD-1/PD-L1 signaling and not mediated through the PD-L1/CD80 or PD-1/PD-L2 axes although further experiments are needed to confirm this. In addition to generating adaptive immunity, radiotherapy has been shown to enhance recognition and antitumor activity of NK cells through increased tumor cell expression of NKG2D (29). Our data reveal that the depletion of NK cells reduced local tumor control at early time points (up to 11 days after completion of radiotherapy) but did not affect overall survival.…”
Section: Discussionmentioning
confidence: 48%
“…The molecular entity to activate NK cells are not known yet, but we discuss here some possible molecular mechanisms for NK cell activation by nickel. The first hypothesis we tested was that nickel ions may activate dendritic cells or macrophages in an unknown stress-sensor pathway and that the stress may activate NK cells through the NKG2D receptor (Kim et al, 2006). With our hands, we could not observe any activation of macrophages and dendritic cells by the treatment with nickel ions.…”
Section: Discussionmentioning
confidence: 55%
“…AP-2 , however, repressed the expression of ULBP1 by binding to the GC(4)/AP-2 site and interfering with the binding of Sp3 and Sp1 to the ULBP1 promoter (Lopez-Soto et al, 2006). It has been shown that heat shock and ionizing radiation treatment can induce the expression of ULBP1/2/3 in human cancer cell lines; HSP 70 is induced by heat shock but not by ionizing radiation (Kim et al, 2006). Human cytomegalovirus (HCMV) can also induce the expression of ULBP1/2/3 proteins that are predominantly localized in the endoplasmic reticulum of infected fibroblasts together with UL16 (Rolle et al, 2003).…”
Section: Ligands Of Nkg2d-ulbpsmentioning
confidence: 99%
“…These molecules exhibit highly restricted expression in healthy tissues but are widely expressed on epithelial tumors. In hematological malignancies they are upregulated in nontumor and tumor cells by genotoxic stress (Kim et al, 2006;Venkataraman et al, 2007). MICB contain putative heat shock elements (HSE) that are prototypic transcription inducer sites in heat shock protein-70 (HSP70) genes and that bind activated trimeric heat shock factor protein-1 (HSF1).…”
Section: Ligands Of Nkg2d-micmentioning
confidence: 99%